Acute Sheehan’s Syndrome Presenting with Hyponatremia Followed by a Spontaneous Pregnancy - Maria M. Pineyro; Leonardo Diaz; Macarena Guzzetti; Mariana Risso; Jimena Pereda (Case Reports in Endocrinology)
Background. Acute Sheehan’s syndrome is rare, as well as hyponatremia as its initial manifestation. In addition, spontaneous pregnancy in patients after Sheehan’s syndrome is unusual. To our knowledge, no cases of spontaneous pregnancy after acute Sheehan’s syndrome have been reported. We describe a case of Sheehan’s syndrome that presented with acute hyponatremia and a spontaneous pregnancy. Case. A 34-year-old female developed blood loss during delivery, which required a blood transfusion. On day seven postpartum, she presented with headaches, lethargy, and difficulty in breastfeeding. The workup showed hyponatremia (118 mEq/l), secondary hypothyroidism, and low prolactin levels. Magnetic resonance imaging showed pituitary necrosis. She was treated with NaCl, hydrocortisone (cortisol results were not available), and levothyroxine. Laboratory tests six weeks after discharge showed low IGF-1 and 8 AM cortisol and normal FT4, LH, FSH, and PRL levels. She was able to partially breastfeed until 4 months postpartum. Regular menstrual cycles started three months later. She became spontaneously pregnant one year later. Conclusion. Acute Sheehan’s syndrome should be considered in the evaluation of postpartum patients with suggestive symptoms. Physicians should be aware that hyponatremia could be an initial manifestation of Sheehan’s syndrome, which requires a high index of suspicion for diagnosis. Spontaneous pregnancy can occur after acute Sheehan’s syndrome.